Remimazolam in Modern Anesthesia: Mechanisms, Organ-Independent Pharmacokinetics, Clinical Evidence, and Safety - He, Jiansheng; Li, Shunlian; Li, Qiao; Zhang, Hang; Deng, Junze; Gao, Wei (Journal of Contemporary Medical Practice, 2025)
Remimazolam is an ultra–short-acting benzodiazepine that positively modulates GABA_A receptors and is rapidly hydrolyzed by nonspecific tissue carboxylesterases to an inactive metabolite, yielding organ-independent clearance, rapid onset and offset, and generally stable hemodynamics; its effects are promptly reversible with flumazenil. Accruing evidence across “painless” endoscopy, perioperative general anesthesia, and ICU sedation shows non-inferior procedural success to propofol or midazolam—with fewer hypotensive and respiratory events and faster cognitive recovery in gastrointestinal endoscopy—and emerging feasibility in ambulatory gynecologic procedures and awake neurosurgery. Practical considerations include the absence of intrinsic analgesia (necessitating opioid co-administration), heightened pharmacodynamic sensitivity in older or frail patients, reduced clearance in severe hepatic impairment, and the potential for re-sedation after antagonism. Adverse events largely mirror class effects (hypoxemia, blood-pressure perturbations), while serious hypersensitivity and clinically meaningful effects on cardiac repolarization appear rare at therapeutic exposure. This review integrates mechanism, pharmacokinetics, dosing strategies, clinical efficacy, and safety to guide rational use of remimazolam in modern, comfort-oriented anesthesia, and highlights priorities for rigorous trials in organ dysfunction and critical illness where putative anti-inflammatory actions remain to be validated.